Assessing ornamental function of the white wing stripe in the Great Tit Parus major - Katarzyna Janas (9181988) (2025)
One of the key puzzles in evolutionary ecology is why some animals display multiple sexual ornaments. To tackle this question in species with complex plumage patterns, it is necessary to know which colour patches are sexually selected, yet the role of less conspicuous ornaments is under-studied. Here, we investigated the potential ornamental role of so far unstudied wing stripe of the Great Tit Parus major. We analysed spectral characteristics of the white dot and adjacent grey area of the greater coverts, jointly forming the conspicuous white wing stripe. We also measured other ornamental traits: the melanin-based cap and tie and the carotenoid-based breast plumage. We aimed to examine sexual dichromatism within the wing stripe, identify its position in the correlation structure of other Great Tit colour traits and examine assortative mating based on analysed traits. We found that all analysed greater covert characteristics were more elaborate in males. However, visual models indicated that the noticeable contrast was present only within the grey part of the outer vane and not within the dot. Further, we observed a positive within-pair correlation of the UV chroma of white dots and the grey part of greater coverts, which may hint to non-random mate-choice based on these traits. Our finding suggests that the Great Tit wing stripe, together with the adjacent grey part of the greater coverts, might belong to the multicomponent sexual signal.